2010
DOI: 10.1111/j.1755-5949.2010.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Dopamine in Schizophrenia

Abstract: Presynaptic dopamine (DA) transmission has been measured in schizophrenia using different paradigms aimed at providing estimates of the integrity or the activity of the presynaptic dopaminergic neuron. RESEARCHERS HAVE MEASURED: (1) DA synthesis capacity with [(18) F]DOPA, a measure of the activity of dopa decarboxylase, (2) DA release with studies measuring the impact of a DA releasing stimulant challenge on the binding of a D(2) receptor radiotracer, (3) D(2) baseline occupancy by DA, a measure of baseline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 66 publications
3
36
0
1
Order By: Relevance
“…44 Similarly, genetic studies addressing the potential association between schizophrenia and the 40-bp VNTR polymorphism in the 3#-UTR (untranslated region) of the DAT gene (SLC6A3) showed negative results (for a meta-analysis see 45 ). Our finding suggests that the increased presynaptic striatal DA activity in schizophrenia indicated by other imaging parameters (for systematic reviews see [12][13][14] ) is not secondary to dysfunctional DAT or an alteration in the density of dopaminergic terminals. In the companion paper published in the present issue, we present the first quantitative meta-analysis addressing the functional integrity of striatal presynaptic dopamine neurotransmission.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…44 Similarly, genetic studies addressing the potential association between schizophrenia and the 40-bp VNTR polymorphism in the 3#-UTR (untranslated region) of the DAT gene (SLC6A3) showed negative results (for a meta-analysis see 45 ). Our finding suggests that the increased presynaptic striatal DA activity in schizophrenia indicated by other imaging parameters (for systematic reviews see [12][13][14] ) is not secondary to dysfunctional DAT or an alteration in the density of dopaminergic terminals. In the companion paper published in the present issue, we present the first quantitative meta-analysis addressing the functional integrity of striatal presynaptic dopamine neurotransmission.…”
Section: Discussionmentioning
confidence: 72%
“…1,10 Over the past years, neurochemical imaging techniques have enabled the striatal presynaptic dopaminergic system to be independently characterized in vivo. 11 In particular, the development of new radiotracers combined with single photon emission computed tomography (SPECT) or positron emission tomography (PET) techniques has allowed accurate investigations of striatal presynaptic dopaminergic alterations in schizophrenia (for reviews see [12][13][14]. Different indexes of presynaptic dopamine neurotransmission such as dopamine synthesis capacity studies 15 and dopamine release 16 /depletion 17 studies have generally shown significant alterations in the striatal presynaptic dopaminergic function in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Electron micrographs of immunostained rat neostriatal D 2 receptors indeed revealed their location in synaptic structures as well as in extrasynaptical regions Hersch et al 1995). Yet, no information about their relative abundance in both locations could be provided, and present opinions about which population is physiologically active in the striatum are sometimes even diametrically opposite (Rice and Cragg 2008;Miyake et al 2010). In this respect, issues like release, uptake, and diffusion will greatly affect the free dopamine concentration and time-wise changes thereof in those distinct locations (Kawagoe et al 1992;Garris et al 1994;Cragg and Rice 2004;Schultz 2007).…”
Section: Impact Of the Antipsychotic Dissociation Rate On D 2 Receptomentioning
confidence: 97%
“…Via these connections, the NAcc modulates dopaminergic input to the dorsal striatum, 3 and striatal dopamine (DA) dysfunction is a hallmark characteristic of the disorder. 4 Though many studies have implicated the NAcc in SZ, none have been able to describe its circuitry.…”
mentioning
confidence: 99%